Andrej Melicherčík - osobnosť v dobe, doba v osobnosti - Hlôšková, Hana (Ethnological studies, 2021)
Title in English: Andrej Melicherčík - personality in time, time in personality. The publication is dedicated to one of the founding personalities of modern professional ethnography and folklore studies - prof. PhDr. A. Melicherčík, CSc. (1917-1966). The author has collected and interpreted numerous factual data about Melicherčík´s university studies at the Faculty of Arts of the Slovak University, but especially about his work at Matica slovenská, at the Slovak Academy of Sciences and Arts and at the Faculty of Arts of Comenius University. She characterizes his numerous activities in the field of organization of scientific life and pedagogical work. The author pays special attention to the methodological approaches that A. Melicherčík applied in his scientific work - functional structuralism and historical materialism. In both approaches, he was the initiator of their application in ethnography and folklore studies in Slovakia. The author analyses his work chronologically - studies, monographs and synthetic publications in terms of concepts, research topics and the organizational grasp of their research and publication. She points out the possible influences of scientific personalities (P. G. Bogatyriov, B. Schier et al.), as well as the non-scientific circumstances that influenced Melicherčík's understanding of the subject, methods and instrumentalization of ethnography and folklore studies.